Insights of carbon assimilation and allocation in young cork oak (Quercus suber L.) plants using Carbon‐14. Issue 3 (26th August 2019) - Nóbrega, Carla; Marques, Helena; Moreira, Tomaz
Abstract : 14 C methods were applied to young, woody, branched and well‐watered cork oak ( Quercus suber L.) plants to determine carbon assimilation and its distribution among plant organs. Carbon assimilation rates by attached leaves clamped in a foliar 14 CO2 assimilation chamber containing 3.7 × 10 4  Bq of a portable ventilated diffusion porometer were measured at different 14 CO2 pulse‐labeling periods (15, 30, 45, 60 and 120 s) in summer. Allocation of recently fixed C by attached leaves within plants was evaluated 7 days after a 60‐min of 5.6 MBq of 14 CO2 pulse‐labeling in late winter. 14 CO2 pulse‐labeling was separately induced on leaves of a lower branch, two opposite branches at the same lower level, a middle branch and a top branch. 14 C activity incorporated into the plants was measured by liquid scintillation and autoradiography. Our results show the optimum 14 CO2 pulse‐labeling period is between 15 and 30 s, which corresponds to 9.81 ± 0.15 and 9.16 ± 0.12 µmol m −2 s −1 C assimilation rates in summer, respectively. The investment of current assimilates ranged from 18 to 29% in leaves, 1 to 7% in lateral branches, 0 to 3% in the stem and over 65% in roots, in late winter. Roots displayed the greatest sink strength for the total 14 C recovered by whole‐plants. These results were expected because the trial was done in winter, when cork oak does not produce their leaves. Our results highlight the contribution of current assimilates for growth and maintenance of roots, in young woody plants under Mediterranean climate.